Convenience, satisfaction, health-related quality of life of once-weekly 70 mg/m 2 vs. twice-weekly 27 mg/m 2 carfilzomib (randomized A.R.R.O.W. study) - Moreau, Philippe; Kumar, Shaji; Boccia, Ralph; Iida, Shinsuke; Goldschmidt, Hartmut; Cocks, Kim; Trigg, Andrew; Zahlten-Kumeli, Anita; Yucel, Emre; Panjabi, Sumeet S.; Dimopoulos, Meletios (Leukemia, 2019)
We compared patient-reported outcomes (PROs) with once-weekly carfilzomib 70 mg/m2 (Kd70 mg/m2) vs. twice-weekly carfilzomib 27 mg/m2 (Kd27 mg/m2) plus dexamethasone in relapsed or refractory multiple myeloma (RRMM). Patient-reported convenience/satisfaction collected at Cycle 2, Day 1 was compared between groups using logistic regression. European Organization for Research and Treatment of Cancer QOL Questionnaire (QLQ-C30), MM-module (QLQ-MY20), and EuroQoL-5 Dimensions-5 Levels (EQ-5D-5L) questionnaires were administered at baseline, then every other cycle. PROs were compared between groups using mixed models for repeated measures. Times from randomization to first deterioration (TTD) in scores were analyzed using Cox regression. PRO analyses included 469 patients. Once-weekly Kd70 mg/m2 patients reported greater convenience (odds ratio [OR], 4.98; p < 0.001) and satisfaction (OR, 2.41; p = 0.059) vs. twice-weekly Kd27 mg/m2. The mixed models for repeated measures demonstrated no clinically meaningful differences in scores between treatment arms. Clinically meaningful deterioration in QLQ-C30 Global Health Status/QOL rates were 34.2% (once-weekly Kd70 mg/m2) vs. 40.3% (twice-weekly Kd27 mg/m2). TTD was longer for once-weekly Kd70 mg/m2 vs. twice-weekly Kd27 mg/m2 for QLQ-C30 fatigue (HR, 0.79; p = 0.035), QLQ-MY20 disease symptoms (HR, 0.67; p = 0.008), EQ-5D-5L index score (HR, 0.58; p = 0.002), and EQ-5D-5L Visual Analog Scale (HR, 0.75, p = 0.031). Once-weekly Kd70 mg/m2 improved convenience/satisfaction, and reduced HRQOL deterioration vs. twice-weekly Kd27 mg/m2, supporting convenient, once-weekly Kd70 mg/m2 dosing in RRMM.